2018
DOI: 10.1007/s10040-017-1716-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of multiple-isotope and groundwater-age data to identify factors affecting the extent of denitrification in a shallow aquifer near a river in South Korea

Abstract: The extent of denitrification using multiple isotopes, groundwater age, and physicochemical data for groundwater was compared in a small agricultural area near a river in Yangpyeong, South Korea. In 2014, the shallow groundwater at one site had high concentrations of NO3-N (74-83 mg L -1 ). The δ 15 N-NO3 values for groundwater in the study area ranged between +9.1 and +24.6‰ in June and +12.2 to +21.6‰ in October. High δ 15 N-NO3 values (+10.7 to +12.5‰) in both sampling periods indicated that the high concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The average δ O values were 2.6 ± 2.5‰ and 19.3 ± 2.6‰ for inorganic fertilizer (IOF, n = 19), 14.7 ± 7.7‰ and 5.9 ± 4.9‰ organic fertilizers (OF, n =30), and 10.9 ± 6.7‰ and 16.0 ± 6.1‰ for plant-based compound fertilizer (PCF, n = 24), respectively. The combined δ O values of nitrate from previous studies (Lee et al, 2008;Koh et al, 2010;Choi et al, 2011;Cheong et al, 2012;Shin et al, 2014;Kim et al, 2015;Kaown et al, 2018) in South Korea superimposed on the revised fields of nitrate from fertilizers determined in this study. Main factors determining the isotopic ranges were shown in italic.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The average δ O values were 2.6 ± 2.5‰ and 19.3 ± 2.6‰ for inorganic fertilizer (IOF, n = 19), 14.7 ± 7.7‰ and 5.9 ± 4.9‰ organic fertilizers (OF, n =30), and 10.9 ± 6.7‰ and 16.0 ± 6.1‰ for plant-based compound fertilizer (PCF, n = 24), respectively. The combined δ O values of nitrate from previous studies (Lee et al, 2008;Koh et al, 2010;Choi et al, 2011;Cheong et al, 2012;Shin et al, 2014;Kim et al, 2015;Kaown et al, 2018) in South Korea superimposed on the revised fields of nitrate from fertilizers determined in this study. Main factors determining the isotopic ranges were shown in italic.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, our results revealed that the nitrate sources in groundwater collected from eastern part of the study area were mainly derived from organic fertilizer including manure, while those in groundwater collected from the other parts was attenuated by denitrification processes (Kaown et al, 2018). A study conducted in mid-western South Korea investigated the sources of nitrate in the shallow groundwater of an agricultural area, and indicated that it is derived predominantly from several sources; i.e., septic waste, inorganic fertilizers, and atmospheric deposition (Koh et al, 2010).…”
Section: Application For Identifying Nitrate Sourcesmentioning
confidence: 74%
See 1 more Smart Citation
“…Groundwater in shallow unconfined groundwater systems is easily contaminated by nitrate because of high vulnerability to pollution from the surface 6,7,8 . However, besides the fact that contamination is usually less effective in deep wells 9 , in some cases, nitrate contamination can also appear in deeper parts of the flow system 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The isotopic composition of nitrate, represented by δ 15 N-NO3 and δ 18 O-NO3 values, can be used to distinguish nitrate sources in groundwater 7,19,20 . This technique is also used to document denitrification in the system 8,17,21 . The traditional physical and chemical measurements (water level, major ion composition, geochemical investigation, etc.)…”
Section: Introductionmentioning
confidence: 99%